Growth impairment in very low birthweight children at 12 years: correlation with perinatal and outcome variables. Issue 3 (November 1996) - Powls, A; Botting, N; Cooke, R W; Pilling, D; Marlow, N
Abstract : AIM: To compare the growth of very low birthweight (VLBW) children in early adolescence with that of their normal birthweight peers; to examine the role of factors contributing to growth-parental height, perinatal variables, bone maturity and sexual maturation; to examine the correlation between head growth and cognitive and educational outcome. METHODS: Standing and sitting heights, weight, occipito-frontal circumference (OFC), skinfold thicknesses and pubertal staging were assessed in 137 VLBW children and 160 controls at 11-13.5 years of age. Ninety six (70%) of the VLBW children had their bone age assessed using the TW2 method. Reported parental heights were obtained by questionnaire. All children had standardised tests of cognitive and educational ability. Perinatal data had been collected prospectively as part of a longitudinal study. RESULTS: VLBW children had lower heights, weight, and OFC. Skinfold thicknesses were no different. The children's short stature was not accounted for by difference in parental height, degree of pubertal development, or by retarded bone age. Indeed, the TW2 RUS score was significantly advanced in the VLBW children. Using the bone ages to predict final adult height, 17% have a predicted height below the third centile and 33% below the tenth. Weight was appropriate for height, but there was a residual deficiency in OFC measurements after taking height into account. In the VLBW group smaller head size was associated with lower IQ and mathematics and reading scores. CONCLUSIONS: Growth problems persist in VLBW children and final heights may be even more abnormal than present heights suggest. VLBW children have smaller OFCs than expected from their short stature alone and this may be associated with poorer educational and cognitive outcomes.